Cardiovascular Risk Profile in Health Cadres in Jatinangor, West Java - Badai Bhatara Tiksnadi; Rien Afrianti; Yulia Sofiatin; Arif Ridha; Faris Yuflih Fihaya; Rully M. A. Roesli; Mohammad Rizki Akbar (Althea Medical Journal, 2019)
Background: Cardiovascular disease has very high morbidity and mortality, therefore, prevention of this disease becomes a national priority in the health programs. Health cadres, as an agent in community primary prevention, should have a good health condition. This study aimed to describe the cardiovascular risk profile in health cadresin Jatinangor, West Java.Methods: This was a cross-sectional study, conducted in Cilayung Village, Jatinangor, in September 2018. Consecutive sampling was performed on 20 health cadres aged 25 - 64 years old who did not have previous cardiovascular events such as coronary heart disease or stroke. Clinical data were collected consisting of blood pressure, body mass index (BMI), random blood glucose, history of diabetes mellitus, physical activity and active smoking habits. Cardiovascular risk was assessed using Jakarta cardiovascular scores and European Relative Risk Score.Results: Only 17 of 20 health cadres fulfilled the inclusion criteria with a systolic and diastolic blood pressure of 133.5±27.8 mmHg and 81.1±14.8 mmHg, respectively, and BMI of 27.4±5.3 kg/m2.The risk of cardiovascular disease in healthy cadres was at low (47.1%), moderate (41.2%) and high risk (11.7%). The average of the European Relative Risk score was 1.88±0.9. BMI >30 has a 40% high risk of cardiovascular disease.Conclusions: Most of the health cadres in Jatinangor, West Java have a low and moderate risk of cardiovascular disease, even though there is a small percentage that is at a high risk. The awareness for prevention and management programs for risk factors needs to be raised among health cadres. .